Silver Ion Promoted, PdII‐Catalyzed Arylation of Arenes with a Free Amine as Directing Group in Aqueous Medium. Issue 49 (25th October 2013) - Liang, Zunjun; Yao, Jinzhong; Wang, Kai; Li, Haoran; Zhang , Yuhong
Abstract Palladium(II)‐catalyzed arylation of arenes with aryl boronic acids and a free amine as directing group in aqueous medium has been developed. High reactivity and chemoselectivity for the formation of carbon–carbon bonds were achieved by the use of soluble silver salts. The addition of water is crucial to improve the arylation yield.